The novel mechanism of financing effect on companies development empirical study - Siwei Tao; Xiuling Yuan (PLoS ONE, 2025)
As China’s economy continues to expand rapidly, the demand for capital among enterprises has surged, leading to an increased preference for short-term loans intended for long-term investments. An analysis of relevant data reveals that utilizing short-term financing for long-term projects positively influences the leverage of non-financial listed companies. Notably, private enterprises experience greater benefits compared to their state-owned counterparts. While short-term loans effectively enhance short-term leverage, their impact on long-term leverage appears to be minimal. Consequently, it is advisable for businesses to select financing strategies that align with their specific circumstances and to enhance their financial management practices to create new funding avenues. Additionally, there is a call for the government to bolster support for private enterprises. These findings hold significant implications for guiding financial decision-making and management in enterprises.